Semiotics and Experiences on Food in the Philippines - Mangompit, Rowanne Marie M. (Randwick International of Social Science Journal, 2024)
This paper aimed to determine and analyze the experiences on food in conversations specifically on food that they associate with family bonding (get-together) and festivities (town fiesta), and categorize the themes of associations on food choices. Ferdinand de Saussure’s (Dewanti, 2023) signifier and signified concepts were used in analyzing the association on food while the experiences of food during family bonding and festivities were categorized by theme using the thematic analysis template of Brooks, McCluskey, Turley & King (2015). This study used the descriptive research method in analyzing food experiences in conversations through one-on-one interviews and group interviews. Conversation analysis was used as the approach in gathering the data. Results of this study revealed the predominance of meat (chicken and pork especially lechon) pancit, and staple food represented by puto and bibingka. In addition, the food choices are signifiers of the following signified: namely, strengthening the family ties, longevity, prosperity, love, joy/happiness, and simplicity and adaptability. Finally, the family tradition is manifested in passing the recipe from the older generation to the younger generation, offering food for the dead, expressing gratitude before eating around the table, looking beyond the taste of food during family bonding. The Filipino food culture has been preserved through passing the kind of food prepared during family bonding as food symbolizes longevity, love, togetherness, strengthening family ties, and simplicity. The choice of food could be attributed to religious beliefs, financial status, and nostalgia.